Esotericism and narrative : the occult fiction of Charles Williams - Roukema, Aren. (Aries Book Series, 2018)
Esotericism and Narrative: The Occult Fiction of Charles Williams situates the life and fiction of the Inkling Charles Williams in the network of modern occultism, with special focus on his initiatory experiences in A.E. Waite's Fellowship of the Rosy Cross . Aren Roukema evaluates fictional projections of magic, kabbalah, alchemy and ritual experience in Williams's seven novels of supernatural fantasy. From this specific analysis, he develops more broadly applicable approaches to the serious expression of religious experience in fiction. Roukema shows that esoteric knowledge has frequently been blurred into fiction because of its inherent narrativity and adaptability, particularly by authors already attracted to the syncretism, multivalence and lived fantasy of the modern occult experience.